The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/atmos9020076
|View full text |Cite|
|
Sign up to set email alerts
|

Recent Advances in Atmospheric Chemistry of Mercury

Abstract: Mercury is one of the most toxic metals and has global importance due to the biomagnification and bioaccumulation of organomercury via the aquatic food web. The physical and chemical transformations of various mercury species in the atmosphere strongly influence their composition, phase, transport characteristics and deposition rate to the ground. Modeling efforts to evaluate the mercury cycling in the environment require an accurate understanding of atmospheric mercury chemistry. We focus this article on rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 115 publications
2
46
0
Order By: Relevance
“…Even though earlier schemes considered oxidation by O 3 as the main pathway in the atmosphere, it was later reported that this reaction is irrelevant in the atmosphere as the gas‐phase reaction is too slow . Since then, the reaction with very reactive bromine atoms is widely assumed to command Hg oxidation globally even though they are present at a low concentration only . The radical produced, HgBr, is an intermediate that can then thermally dissociate back to Hg 0 or be further oxidized by atmospheric radicals such as OH, Br, I, Cl, NO 2 , HO 2 , BrO, IO, and ClO, to form stable Hg II compounds …”
Section: Introductionmentioning
confidence: 99%
“…Even though earlier schemes considered oxidation by O 3 as the main pathway in the atmosphere, it was later reported that this reaction is irrelevant in the atmosphere as the gas‐phase reaction is too slow . Since then, the reaction with very reactive bromine atoms is widely assumed to command Hg oxidation globally even though they are present at a low concentration only . The radical produced, HgBr, is an intermediate that can then thermally dissociate back to Hg 0 or be further oxidized by atmospheric radicals such as OH, Br, I, Cl, NO 2 , HO 2 , BrO, IO, and ClO, to form stable Hg II compounds …”
Section: Introductionmentioning
confidence: 99%
“…These large uncertainties in atmospheric mercury oxidation are related not only to the rate constants of related reactions, but also to the chemical pathways themselves (Si and Ariya 2018). While early modeling of GEM oxidation in the troposphere accounted for a high impact of photochemical smog by considering ozone (O 3 ) and hydroxyl radical (OH) as major GEM oxidants (Seigneur et al 1994, Lin andPongprueksa 2007), more recent modeling studies indicate a major role for the bromine atom (Br) in GEM oxidation on a global scale, and particularly in the marine boundary layer and free troposphere (Lin et al 2004, Holmes et al 2006, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The published paper [1] has been updated to remove instances of copied text from other publications [2][3][4][5][6]. Changes have been made throughout the paper, with the most significant alterations made in Sections 2.1, 2.4, 3.1, 3.2, 3.3, and 4.…”
mentioning
confidence: 99%
“…Ref. [1] is a review article that was invited for the journal Atmosphere. The author Lin Si took the lead in writing the article, although this is the first time she has undertaken writing a review paper.…”
mentioning
confidence: 99%
See 1 more Smart Citation